Efektivitas Media Pembelajaran Digital LiBeRu dalam Membangun Lingkungan Belajar yang Interaktif dan Menyenangkan - Sayuti, Anni Sa’u Latifatas; Berliani, Mercy Kusuma; Lestari, Sri; Saputra, Donny Dwi; Amalia, Himmatul; Istiq’faroh, Nurul; Zahroh, Ulfi Aminatuz (CV. Kurnia Grup, 2025)
This research aims to develop digital-based LiBeRu teaching materials with features such as material E-modules which include encouraging quotes and learning video references and are then equipped with a choice of independent quizzes or quizzes with friends. This type of research is R&D with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The test subjects in this research were class VI students at SD YPI DARUSSALAM Cerme Gresik. Data collection techniques in this research include validation sheets to determine the level of validity, questionnaire response sheets to determine the level of practicability of use to measure the effectiveness of products developed in learning. Data analysis techniques include qualitative data and quantitative data.